Sentinel Lymph Node Biopsy vs. Axillary Lymph Node Dissection for Early-Stage Breast Cancer and Sentinel Lymph Node Metastasis: An Updated Systematic Review and Meta-Analysis With Special Focus on Locoregional Recurrence and Regional Node Irradiation - Sanjit Kumar Agrawal; M. Mohammed Imran; Shivank Sethi; Sanjay Kumar Yadav; Pawan Agarwal; Dhananjaya Sharma (Breast Cancer: Basic and Clinical Research)
Background: The management of early breast cancer patients with metastatic sentinel lymph nodes (SLNs) remains a critical decision point in balancing survival outcomes with surgical morbidities. This study addresses whether sentinel lymph node biopsy (SLNB) with or without regional node irradiation (RNI) can offer comparable survival outcomes to axillary lymph node dissection (ALND). Objectives: To evaluate overall survival (OS), disease-free survival (DFS), locoregional recurrence (LRR), and mortality outcomes of SLNB (with or without RNI) compared with ALND in patients with metastasis-positive SLNs. Design: We have performed an updated meta-analysis of randomized controlled trials (RCTs) comparing SLNB alone or with RNI vs. ALND for early breast cancer patients with metastatic SLNs. Data Sources and Methods: Eligibility criteria included RCTs comparing SLNB ± RNI vs ALND for metastasis-positive SLN. PubMed, EMBASE, the Cochrane library, and online registers were searched for articles comparing SLNB alone vs. ALND for metastasis-positive SLN. Articles were evaluated for risk of bias using Cochrane’s revised tool (RoB). The main summary measures using the random effects model were hazard ratio and risk ratio. Results: Seven RCTs were included in the meta-analysis. Overall survival and DFS were superior in the SLNB group compared to the ALND group. Locoregional recurrence and mortality were comparable between both the groups. After stratifying RCTs with regards to adjuvant RNI, these parameters were still comparable to ALND. Conclusion: This meta-analysis suggests that SLNB, with or without RNI, offers comparable OS and DFS to ALND for early breast cancer patients with metastasis-positive SLNs. However, the inclusion of studies that did not differentiate between micrometastases and macrometastases may introduce bias, particularly when assessing the impact of RNI. The role of RNI remains debated specially in those with macrometastases, and future research should focus on stratified analyses to clarify this. While SLNB represents a viable alternative to ALND, further trials are needed to define the optimal role in subgroups with high-risk tumor biology.